2020
DOI: 10.1590/pboci.2020.143
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of New Biosafety Recommendations for Dental Clinical Practice During COVID-19 Pandemic

Abstract: COVID-19 pandemic implied new biosafety recommendations to avoid dissemination of SARS-CoV-2 virus within healthcare centers. Changes on recommended personal protective equipment (PPE), decontamination protocols and organization of patient demand resulted may result in cost variation. Based on this, the present study aimed to evaluate the economic impact of new biosafety recommendations for oral healthcare assistance during COVID-19. An Activity Based Costing evaluation was used to calculate the acquisition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
3
19
0
12
Order By: Relevance
“…The introduction of these practices was reported by most of the periodontists who responded to the survey in both countries (Tables 2 and 3). It is supposed that such measures may have financial implications, as was previously reported by a recent Brazilian study (Cavalcanti et al, 2020). Furthermore, the difficulty in acquiring common personal protective equipment due to its scarcity and exorbitant cost on the market, as demonstrated recently (Chamorro‐Petronacci et al, 2020; Consolo et al, 2020) and reported by 66.1% of the periodontists in this study, is another negative factor to take into consideration in securing clinical practice after the pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…The introduction of these practices was reported by most of the periodontists who responded to the survey in both countries (Tables 2 and 3). It is supposed that such measures may have financial implications, as was previously reported by a recent Brazilian study (Cavalcanti et al, 2020). Furthermore, the difficulty in acquiring common personal protective equipment due to its scarcity and exorbitant cost on the market, as demonstrated recently (Chamorro‐Petronacci et al, 2020; Consolo et al, 2020) and reported by 66.1% of the periodontists in this study, is another negative factor to take into consideration in securing clinical practice after the pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…Although the data were collected before the onset of the COVID-19 pandemic, the situation of the lack of PPE for oral health professionals may have been worsened recently by the lack of new PPE [ 4 6 ]. One study has pointed out the high increase in costs and the difficulty in purchasing them [ 26 ]. Direct costs in biosafety before COVID-19 were R$0.84 per patient, R$6.69 per care shift, and R$3,413.94 per year [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has pointed out the high increase in costs and the difficulty in purchasing them [ 26 ]. Direct costs in biosafety before COVID-19 were R$0.84 per patient, R$6.69 per care shift, and R$3,413.94 per year [ 26 ]. With the COVID-19 pandemic, the costs increased to R$16.01 per patient, R$128.07 per shift, and R$32,657.96 per year [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that changes in biosafety protocols during the COVID-19 pandemic, the increase in PPE values, and the need to purchase new equipment such as thermometers have significantly increased the costs of dental treatments [27,31].…”
Section: Considerations On Suggested Protocolsmentioning
confidence: 99%